2015
DOI: 10.1007/s13277-015-3732-4
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1-miR-124-RBG2 axis is involved in growth and invasion of HR-HPV-positive cervical cancer cells

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT 1) is a large, infrequently spliced non-coding RNA aberrantly expressed in cervical cancer. But the molecular mechanisms of its oncogenic role are still not quite clear. The present study explored whether there is a competing endogenous RNAs (ceRNAs) mechanism involved in the oncogenic effect of MALAT1. MALAT1 expression was firstly verified in high-risk human papillomavirus (HR-HPV)-positive tumor tissues and cell lines. Its regulation over miR-124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 28 publications
2
86
0
Order By: Relevance
“…MALAT1 was reported to be an endogenous regulator of breast cancer progression by down-regulating miR-124 and activating the CDK4/E2F1 signaling pathway [23]. MALAT1 could modulate GRB2 expression via competing miR-124 to promote high-risk human papillomavirus (HR-HPV)-positive cervical cancer cell growth and invasion [30]. Here, our study further investigated whether MALAT1 could regulate apoptosis of DA neurons in PD by sponging miR-124.…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 was reported to be an endogenous regulator of breast cancer progression by down-regulating miR-124 and activating the CDK4/E2F1 signaling pathway [23]. MALAT1 could modulate GRB2 expression via competing miR-124 to promote high-risk human papillomavirus (HR-HPV)-positive cervical cancer cell growth and invasion [30]. Here, our study further investigated whether MALAT1 could regulate apoptosis of DA neurons in PD by sponging miR-124.…”
Section: Discussionmentioning
confidence: 99%
“…28 Similarly, MALAT1 is abundant in neurons and is implicated in the development and/or maintenance of synapses. 30 One study has also demonstrated that the knockdown of MALAT1 expression inhibited MPTP-induced apoptosis in SH-SY5Y cells and in DA neurons of PD mice. 30 One study has also demonstrated that the knockdown of MALAT1 expression inhibited MPTP-induced apoptosis in SH-SY5Y cells and in DA neurons of PD mice.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124, a major miRNA that is associated with cancer, exerts regulatory effects on various oncogenes and participates in signaling pathways that are closely associated with cancer growth [28–30]. miR-124 exerts tumor suppressive functions on cell proliferation in bladder cancer [31], breast cancer [32] and non-small cell lung cancer [33].…”
Section: Discussionmentioning
confidence: 99%